Effectiveness of a Web-Based eHealth Portal for Delivery of Care to Home Dialysis Patients: A Single-Arm Pilot Study. Issue 1 (September 2018) - Kiberd, James; Khan, Usman; Stockman, Cynthia; Radhakrishnan, Arun; Phillips, Matthew; Kiberd, Bryce A.; West, Kenneth A.; Soroka, Steven; Chan, Christopher; Tennankore, Karthik K.
Background: Improving a patient's experience with their care through an online interface for communication (an eHealth patient portal) has been shown to be beneficial in some studies of chronic disease populations. However, little is known about the effectiveness of an eHealth portal for delivery of care to home dialysis patients. Objectives: Primary: To determine whether an eHealth portal is effective at improving a patient's experience with their home dialysis care. Secondary : (1) To determine whether an eHealth portal improves health-related quality of life for home dialysis patients, (2) to assess patient satisfaction with an eHealth portal and perceived impact on aspects of their home dialysis therapy and health, (3) to determine the acceptability of the eHealth portal software, and (4) to determine the change in telephone usage for communication after patient adoption of an eHealth portal. Design: Single-arm pilot trial with recruitment over a 4-month period. Setting: The multidisciplinary home dialysis clinic in Halifax Nova Scotia Canada. Patients: Adults (>18 years) receiving either home hemodialysis or peritoneal dialysis. Measurements: Consumer quality index (CQI), health-related quality of life using the EuroQol Five Dimensions Questionnaire (EQ-5D), acceptability of the eHealth portal software (using the Acceptability E-scale), and satisfaction/perceived impact (using a modified questionnaire). Methods: A web-based application (McKesson, Canada, RelayHealth®) allowed patients and health care workers to communicate through a secure, password-protected online portal that permitted visualization of the messaging history by patient and provider. Patients and the home dialysis health care team had the ability to send messages related to patient care at any time including proposed changes to medication, instructions after a clinic visit, times of new appointments, upcoming investigations, or questions about care. Patient experience with home dialysis care using the CQI, health-related quality of life using the EQ-5D, acceptability of the eHealth portal software, and satisfaction/perceived impact were assessed at baseline, 6, and 12 months of follow-up (where applicable). Total minutes of telephone communication was assessed prior to and after adoption of the portal. Results: Of the 41 patients who consented to join the portal, 27 (66%) created an online account. At baseline, patients had a positive experience for the care and communication provided by their nephrologist (CQI: 3.63, 95% confidence interval [CI]: 3.50-3.76) and this did not change significantly over the study period. Similar results were observed for the care provided by other nephrology health care team members. Health-related quality of life using the EQ-5D score was 0.80 (interquartile range [IQR]: 0.71-0.83) at baseline and this also did not significantly change over the study period. Patients were satisfied with the eHealth portal (mean Likert scale score of 6.5 ± 0.6 in overall satisfaction, scale ranging from 1 completely dissatisfied to 10 completely satisfied), but only a minority (N = 12) completed a satisfaction questionnaire. Median monthly phone usage decreased from 12.5 to 10 minutes ( P = .02) after adoption of the portal. Limitations: The study is limited by the small sample size, high rate of patient dropout, and limited response rate. Conclusions: In this study of home dialysis patients, we identified that an eHealth communication did not lead to significant improvements in patient experience with home dialysis care. Trial Registration: ClinicalTrials.gov number NCT02128347